LOW POWER BRACHYTHERAPY IN COMBINED TREATMENT IN PATIENTS WITH INTERMEDIATE RISK OF LOCALIZED PROST ATE CANCER - V. A. Biryukov; O. B. Karyakin; O. V. Morov; O. G. Lepilina; D. V. Neledov; D. B. Sanin; G. N. Grishin; M. S. Kalinina (Исследования и практика в медицине)
Objective. Estimation of the effectiveness of low power brachytherapy sources I-125 in the combined treatment in group of patients of intermediate risk of localized prostate cancer.Material and methods. The study included 126 patients with prostate cancer of intermediate risk. 104 patients (83,9%) were conducted low power brachytherapy I‑125 in combination with hormone therapy by analogues of LHWG. 22 patients (16.1%) received external beam irradiation in combination with brachytherapy I‑125 and hormonal treatment. Relapse-free survival of patients was evaluated in accordance with the criteria Phoenix (Nadir PSA + ng/ml). Evaluation of side effects of radiation treatment were carried out according to the RTOG criteria.Results. PSA relapse-free survival in the group of brachytherapy and hormone treatment at the time of observation 5 years amounted to 97.1%. In the group of combined radiation therapy with brachytherapy, and hormonal treatment PSA relapse-free survival rate was 95.5%.In both groups, relapse-free survival was noted in 96,8% of cases. Tumor-specific and overall survival in bothgroups was 100%. The major complications of treatment in both groups were radiation urethritis 1 to 2 degrees in 9.5% of cases (12 patients), urethral stricture in 5 patients (3.9% of cases), acute urinary retention in 1 patient (0.8% of cases) and late radiation rectitis of 2 degree in 1.58% of cases (2 patients).Conclusions. It is possible to draw tentative conclusions about the high rate of survival without progression in both treatment groups on the background of the relatively low frequency of adverse reactions. It is necessary further follow-up for patients with estimating of survival for a longer period.